Analisis surah al-hujurat ayat 11 terhadap penamaan produk halal yang menyerupai minuman beralkohol dalam proses sertifikasi halal di indonesia: studi tafsir maqashidi abdul mustaqim - Faizeh, Faizeh Faizeh (Maliki Interdisciplinary Journal, 2025)
The phenomenon of halal product naming in Indonesia that resembles alcoholic beverages, such as "halal beer" or "halal wine," which has sparked controversy among Muslim communities. The analysis applies a maqāṣidī exegesis approach to Surah al-Ḥujurāt verse 11 from the perspective of Abdul Mustaqim. This verse prohibits mockery, insult, and derogatory labeling that undermines human dignity. Using the maqāṣidī method, the prohibition is extended to the practice of labeling halal products with names resembling prohibited alcoholic symbols. The findings reveal that such naming practices obscure halal identity, create ambiguity (syubhat), and contradict the higher objectives of Islamic law (maqasid al-shari‘ah), particularly in preserving religion (hifz al-din), intellect (hifz al-‘aql), and honor (hifz al-‘ird). This study concludes that halal certification should not only assess ingredients and production processes but must also consider product naming as an ethical, social, and spiritual dimension.